Hyaluronic Acid in Managing Deep Residual Pockets in Stage III-IV Periodontitis: A Randomized Controlled Trial - Jaafar, Mohamad Adib; Vui Ching, Esther Voo; Ali, Sharul Nisha; Subramaniam, Jeyanthi; Ahmad Yaziz, Yuhaniz (Journal of Dentistry Indonesia, 2024)
Objective: The purpose of this study was to determine the adjunctive clinical effect of hyaluronic acid (HA) in the non-surgical treatment of subjects with residual pockets (≥ 6 mm) at the maintenance phase. Methods: 36 systemically healthy subjects in the periodontal maintenance phase were included in this 3-month randomized clinical trial. Subjects received a course of full-mouth, scaling and root debridement (SRD). In the test group (n = 18), HA 0.8% was applied subgingivally immediately after SRD. The control group (n = 18) was treated with SRD only. Subjects in both groups were required to apply HA 0.2% twice a day for 2 weeks. Clinical parameters collected at baseline and 3 months post-treatment were periodontal pocket depth (PPD), bleeding on probing (BOP), and clinical attachment level (CAL). Results: In both groups, all parameters were significantly reduced (p < 0.05) after treatment. Subjects treated with HA 0.8% showed a greater gain in mean CAL and higher percentage of ‘healthy pocket’ (PPD ≤ 3 mm) than the control group. However, no statistical difference was observed. Conclusion: The overall results show that treatment with HA 0.8% has a potential improvement in periodontal health.